2022
DOI: 10.1039/d2tc01886a
|View full text |Cite
|
Sign up to set email alerts
|

Highly stretchable and stretch-induced fluorescence chromism self-healing materials based on boroxine and dynamic imine bond

Abstract: A new self-healing luminescent polymer called PDMS-DPBA-5000 was synthesized by combining the double covalent bond of boroxine with imine bond. The formation of boroxine bond will offer a luminescence center,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The polymer could fully recover its mechanical properties after healing for 12 h at 70 °C, or healing at room temperature with 70% RH for 12 h. In another study, the elongation of boroxine system was tuned by the incorporation of PDMS and dynamic imine bond. 123 The combination of boroxine and imine bonds with flexible PDMS backbone achieved elongation at break of 4200% and tensile strength of 0.25 MPa, as well as self-healing at room temperature in 20 min. Similarly, self-healing polymers based on dynamic-covalent boronic esters exhibited facile reversibility of the networks and allowed intrinsic self-healing under ambient conditions.…”
Section: Self-healing Materials With Covalent Dynamic Bondsmentioning
confidence: 98%
See 1 more Smart Citation
“…The polymer could fully recover its mechanical properties after healing for 12 h at 70 °C, or healing at room temperature with 70% RH for 12 h. In another study, the elongation of boroxine system was tuned by the incorporation of PDMS and dynamic imine bond. 123 The combination of boroxine and imine bonds with flexible PDMS backbone achieved elongation at break of 4200% and tensile strength of 0.25 MPa, as well as self-healing at room temperature in 20 min. Similarly, self-healing polymers based on dynamic-covalent boronic esters exhibited facile reversibility of the networks and allowed intrinsic self-healing under ambient conditions.…”
Section: Self-healing Materials With Covalent Dynamic Bondsmentioning
confidence: 98%
“…It is also reported that combining boroxine with hydrogen bonding groups formed iminoboronate/boroxine-based polyurethane network with tensile strength of 11 MPa and elongation-at-break of 3%. The polymer could fully recover its mechanical properties after healing for 12 h at 70 °C, or healing at room temperature with 70% RH for 12 h. In another study, the elongation of boroxine system was tuned by the incorporation of PDMS and dynamic imine bond . The combination of boroxine and imine bonds with flexible PDMS backbone achieved elongation at break of 4200% and tensile strength of 0.25 MPa, as well as self-healing at room temperature in 20 min.…”
Section: Representative Intrinsic Self-healing Polymersmentioning
confidence: 99%
“…Wang et al employed (3,5-diformylphenyl) boronic acid (DPBA) and NH 2 -PDMS-NH 2 to acquire PDMS-DPBA fluorescent self-healing elastomer based on double covalent bonds, as presented in Figure 6. [46] Boroxine bond provided a luminescence center and dynamic imine bond offered self-healing property. Meanwhile, the film also showed stretch-induced discoloration from green to cyan, which was attributed to the transition of fluorescence center from aggregation to dispersion state.…”
Section: Othersmentioning
confidence: 99%
“…Figure 6. a) The structure and the dynamic process of PDMS-DPBA, b) the mechanism for the self-healing process,and c) schematic illustration of stretch-induced fluorescence chromism. Reproduced with permission [46]. Copyright 2022, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…32,57−61 Moreover, the dynamic equilibrium between boroxine and boronic acids under mild conditions ensures boroxines to be used to prepare self-healable, processable, and even chemically recyclable supramolecular thermosets. 23,24,32,52,60 Therefore, we believe that high-performance PI-based supramolecular thermosets can be conveniently fabricated using boroxines as cross-linkers. Herein, we report PI-based supramolecular thermosets that can achieve rapid depolymerization at room temperature in mild acidic aqueous solutions.…”
Section: ■ Introductionmentioning
confidence: 99%